2022
DOI: 10.4149/neo_2022_220329n348
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of EGFR-TKIs in advanced squamous cell lung cancer

Abstract: We aimed to explore the treatment efficacy of first-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) for lung squamous cell carcinoma (SCC) patients and identify potential beneficial subgroups of EGFR-mutated lung SCC patients in this study. Between February 1 st , 2013 and December 1 st , 2021, 657 advanced lung SCC patients were enrolled at Zhejiang Cancer Hospital. Amplification refractory mutation system PCR or next-generation sequencing were used to detect gene abnormality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Because EGFR TKI, especially erlotinib (Tarceva) is indicated for the second‐line treatment or beyond after the failure of previous chemotherapy for NSCLC (not limited to adenocarcinoma) 23,24 . Recently, a real‐world study in China exhibit survival benefit with first generation EGFR‐TKI in LUSC harboring EGFR mutation whether as first‐line treatment or beyond 25 . In the final analysis of LUX‐Lung‐8 trial, both afatinib and erlotinib showed survival benefit and some of the patient being survived after more than 3 years 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because EGFR TKI, especially erlotinib (Tarceva) is indicated for the second‐line treatment or beyond after the failure of previous chemotherapy for NSCLC (not limited to adenocarcinoma) 23,24 . Recently, a real‐world study in China exhibit survival benefit with first generation EGFR‐TKI in LUSC harboring EGFR mutation whether as first‐line treatment or beyond 25 . In the final analysis of LUX‐Lung‐8 trial, both afatinib and erlotinib showed survival benefit and some of the patient being survived after more than 3 years 26 .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Recently, a real-world study in China exhibit survival benefit with first generation EGFR-TKI in LUSC harboring EGFR mutation whether as first-line treatment or beyond. 25 In the final analysis of LUX-Lung-8 trial, both afatinib and erlotinib showed survival benefit and some of the patient being survived after more than 3 years. 26 In addition, EGFR TKI is a welltolerated and available treatment option.…”
Section: Multivariable Analysis Of Pfs and Osmentioning
confidence: 99%
“…Platinum-based chemotherapeutic agents (cisplatin and carboplatin) have been recently approved for the treatment of lung SCC and non-SCC in combination with anti-programmed death receptor 1 (PD-1) monoclonal antibodies (pembrolizumab, atezolizumab, bevacizumab and nivolumab) targeting T cell immune checkpoints [ 22 , 23 ]. Furthermore, the EGFR tyrosine kinase inhibitor (EGFR-TKI), osimertinib, dacomitinib, afatinib, gefitinib and erlotinib, have shown superior clinical survival benefits in lung SCC and/or ADC patients with EGFR mutation [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%